Impact of the Updated Guideline for Pediatric Brain Death Determination on Current Practice. (June 2022) - Krawiec, Conrad; Mysore, Mohan R.; Mathur, Mudit; Fang, Xinying; Zhou, Shouhao; Thomas, Neal J.; Nakagawa, Thomas A.
Background: A guideline to determine pediatric brain death was updated in 2011. It is unknown how pediatric intensivists have accepted and adopted the revised guideline into clinical practice.Methods: We surveyed US pediatric critical care attending physicians July 2013 to September 2013 and February 2020 to May 2020. Brain death testing practices and utilization of the 2011 pediatric and neonatal brain death guideline were assessed.Results: The 2020 respondents found that the revised pediatric brain death guideline were useful in clinical practice (93.7% vs 83.3%, P  = .0484) and provided more consistency and clarity (73.2% vs 63.1%, P  = .0462) when compared to 2013 respondents.Conclusion: This study demonstrates that with defined criteria, survey participants reported increased clarity and consistency. Findings from our study indicate that in clinical practice there is no significant deviation from the minimum requirements to determine brain death in children as outlined in the 2011 guideline.